EFEKTIVITAS TEPUNG DAUN SAMBILOTO (Andrographis paniculata nees) SEBAGAI ANTIBAKTERI TERHADAP PERFORMANS BROILER YANG TERINFEKSI Escherichia coli - Rosa Tri Hertamawati; Niswatin Hasanah; Adline Putri Sabrina (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
Rapid broiler development is one of the reason farmers’ choice in raising broiler. The effect broiler become weak because of diseases even come from bacteria or viruses. One of the diseases which are leaded by bacteria which attack broiler oftenly is colibacillosis. The aim of this experiment was to examine the addition of sambiloto leaf meal on feed to the inhibition of bacterial development inside the body of infected Escherichia coli broiler toincrease broilers performance. This experiment used 100 day old chicks (DOC) of Cobb strain which were kept for five weeks. The experiment used completely randomized design with five treatments and four replications consisting of 5 broilers in each replication. The treatments were P0 = control (healthy broiler), P1 = P0 infected with Escherichia coli, P2 = P1 + 0,2% sambiloto leaf meal, P3 = P1 + 0,4% sambiloto leaf meal, P4 = P1 + 0,6% sambiloto leaf meal. The data were analyzed with analysis of variance. The variables observed were feed consumption, body weight gain, final body weight, feed conversion ratio, mortality, and total colony bacteria in broiler excreta. The result showed that sambiloto leaf meals 0.6% have a significant effect in decreasing bacteria. Keywords: Antibacterial, Broilers, Eschericia coli, Performance, Sambiloto leaf meal